ANALISIS POLA ASUH ORANG TUA DENGAN STATUS GIZI ANAK PRASEKOLAH DI RT 01 RW 01 DESA MANUNGGAL BANGKALAN MADURA - Firdaus, Firdaus; M. Muafif, M. Muafif (Unusa Press, 2016)
Preschool children the brain needs a steady supply of nutrients in the growth, nutritional status causing the problem is parenting a child who is less precise. Data Riskesdas at 2010 nutritional status of children in Indonesia showed the prevalence of malnutrition 13%, 5.8% more nutrition, malnutrition 4.9%. The research purposes to know parenting parents relationship with nutritional status of preschool children at Desa Manunggal Kecamatan Klampis Bangkalan Madura.This research are analytic observational, cross-sectional approach. Independent variables and the dependent parenting nutritional status. Populations of all the parents who have preschool children aged 3-5 years at RT 01 RW 01 Manunggal Desa Bangkalan 23 pairs with the sample 22 respondents using simple random sampling. The research instrument questionnaire, data processing analysis Spearman rank test significance level of 0.05.The results showed the majority of respondents (54.5%) have poorly parent and the majority of respondents (54.5%) have a thin child's nutritional status. Spearman rank test results obtained ρ value = 0.007 <0.05, meaning there is a pattern of parent and nutritional status of preschool children.The better parenting parents increasingly normal nutritional status of children. Expected health workers provide counseling on the importance of appropriate parenting nutritional needs of children and doing the weigh regularly to monitor the nutritional status of children.